(untitled) (Journal of Medical & Health Sciences Review, 2025)
Objectives: The aim of the following study is to analyze the role of body mass index (BMI) as a modifiable risk factor in breast cancer disease. Materials and Methods: This case-control study was conducted in a cross-sectional pattern and data pertaining to all the admitted patients related to breast cancer (cases) and other breast diseases (controls) in the surgical department was collected from July 2024 to December 2024. A total of 252 (126 each for both cases and controls) patients were enrolled in this study either admitted through OPD or emergency. The variables that were included in the study are the following: name, age, contact number, date of admission, medical record number (MR number), type of breast disease and Body Mass index (BMI). Data was collected in a pre-designed proforma, added to Microsoft excel sheet and analyzed through SPSS software version 23.0. The data was described in the form of description, charts and tables. Results: For controls, 68 (54%) patients were overweight (BMI 25.0 to 29.9 kg/m²), and 19 (15.1%) patients were obese (BMI 30 and above kg/m²). For cases, 76 (60.3%) patients were overweight (BMI 25.0 to 29.9 kg/m²), and 28 (22.2%) patients were obese (BMI 30 and above kg/m²). Pearson chi square correlation showed positive association between weight gain and the risk of breast cancer progression (p-value <0.05). Conclusion: Obesity is a potential risk factor for breast cancer in women; therefore, prevention of weight gain and onset of obesity should be avoided to postpone or prevent some kinds of breast cancer.